Reading Comprehension Difficulties on English Descriptive Text - Martina Napratilora; Mardiah; Nova Adi Kurniawan (CV. Kalimasada Group Profesional, 2024)
Research aims were knowing about reading comprehending of reading difficulties on English text and the solutions. It was focus on five reading aspects in comprehending, they were main idea, topic sentence, vocabulary, inference, and referent. This research was a library approach with descriptive qualitative method. Research subject was relevant literatures sources and data on the same issue to reading comprehension difficulties on English text. the research show that learners have problematic in analyzing main point in every paragraph, confused in finding topic sentence, wrong words meaning matching, confused in making inference, could not finding inference in the reading text. From five aspects, the most difficult aspect was identifying main idea and vocabulary understanding because sometime it wrote implicitly. Solving this trouble, as the teachers, it was very important to teach the students using various reading strategies, and various types of reading text. for the students, they need to do more reading practice than before, as many as experiences and background knowledge in reading text, it was very useful to help them in comprehending English reading text. Students also must use reading strategy while reading the text, using dictionary or ask the teacher about unfamiliar words. Keywords: Difficulties; English Text; Reading Comprehension;.